A Multiple-Frequency-Taylor-Model based estimator for dynamic synchrophasor considering decaying DC component. (March 2023) - Xiong, Siyu; Li, Zhili; Guo, Ying; Xiong, Feng; Fu, Ling; Mai, Ruikun
Highlights: MFTDC is proposed as a novelty estimator to improve the estimation accuracy for the fault current, and it can reduce the adverse effects of DDC, dynamic characteristics as well as frequency deviations. A time–frequency domain model-based STFT estimation method is proposed to solve MFTDC equation sets that significantly shorten the response time. Compared with our previous work [26], MFTDC can provide high accuracy and fast response synchrophasor estimations for P-class applications under DDC scenarios. The historical data of frequency estimates are employed to construct the offline coefficient matrices to deal with the adverse effect of the frequency deviations. Abstract: When the grounding fault occurs in power systems, it might stimulate power oscillations and generate decaying dc component (DDC) in the fault currents. Both will cause a sharp drop in the phasor monitoring accuracy of phasor measurement units (PMUs) and even lead operational protection devices to malfunction. Thus, a multiple-frequency-Taylor-model (MFTM)-based dynamic synchrophasor estimator considering DDC (MFTDC) is proposed to overcome the adverse effect by modeling dynamic behavior and DDC. Firstly, several sub-phasors extended by the Taylor series are employed to form the dynamic fundamental component and DDC. Secondly, rough phasor estimations are obtained by DFT filters at multiple frequency bins to establish the MFTDC equation set. Then, all Taylor derivatives of MFTDC can be solved by the least square method. Finally, various IEEE standard P-class test and static/dynamic-state DDC test results of computer, PSCAD/EMTDC, and RTDS-generated signals verify that MFTDC is suitable for the protection applications of power systems. It can yield more accurate phasor estimations of PMUs than that of our previous work and shorten the convergence time to 20.3 ms or less, especially under the dynamic-state DDC scenarios.